Penguatan Implementasi Computational Thinking dalam Pembelajaran Sains Bagi Guru-Guru Sekolah Indonesia Kuala Lumpur - Sugiyanto Sugiyanto; Sugianto Sugianto; Putut Marwoto; Budi Astuti (Universitas Negeri Semarang, 2024)
The essential 21st-century skills, including collaboration, communication, creativity, and critical thinking, are valuable when combined with computational thinking (CT) skills. Teachers at Sekolah Indonesia Kuala Lumpur (SIKL) need to be capable of implementing CT in their teaching. Since CT is relatively new to the learning environment at SIKL, the implementation of CT in science education needs to be strengthened, particularly for science teachers at SIKL. The issue to be addressed is empowering teachers to implement CT in science teaching at SIKL. The partner’s problem-solving method is based on a facilitation-based Action Learning model. This facilitation-based action learning is divided into three stages: preparation, implementation, and evaluation. The activities include programmed workshops and discussions to understand CT, its importance as a fundamental skill across subjects in today’s and future digital era, and the need for SIKL teachers to acquire foundational CT skills. In addition to workshops and discussions, support was provided in the form of workshops for practicing CT integration and evaluating it within science education. This activity involved 30 SIKL teachers from various levels and subject areas. Before the training, only 45% of participants understood CT concepts, and only a few had applied CT, but afterward, 80% of teachers were able to integrate CT into their teaching. Intensive support in planning, implementing, and evaluating CT-based learning had a significant positive impact. Despite challenges due to the participants' diverse educational backgrounds, the facilitation-based Action Learning method proved effective in addressing these differences and enhancing active participation. This initiative is expected to serve as a starting point for broader CT implementation within SIKL.